2022
DOI: 10.1097/j.pain.0000000000002668
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuron–expressed TRPC3 mediates acute and chronic itch

Abstract: Background: Chronic pruritus is a prominent symptom of allergic contact dermatitis (ACD) and represent a huge unmet health problem. However, its underlying cellular and molecular mechanisms remain largely unexplored. TRPC3 is highly expressed in primary sensory neurons and has been implicated in peripheral sensitization induced by proin ammatory mediators. However, the role of TRPC3 in acute and chronic itch is still not well de ned.Methods: RNAscope in situ hybridization and immunohistochemical staining were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…47 Transient receptor potential (TRP) channels, such as TRPA1, TRPV1, TRPV4, and TRPC3, are required for the induction of both pain and itch. 8,14,20,50,52,54,60,86 Limited studies have shown that SPMs alleviate itch by peripheral mechanisms, such as reducing skin inflammation and modulation of TRP channels. Resolvin E1 attenuates murine psoriatic dermatitis, a chronic itch disease, by inhibiting migration of cutaneous dendritic cells and gd T cells.…”
Section: Discussionmentioning
confidence: 99%
“…47 Transient receptor potential (TRP) channels, such as TRPA1, TRPV1, TRPV4, and TRPC3, are required for the induction of both pain and itch. 8,14,20,50,52,54,60,86 Limited studies have shown that SPMs alleviate itch by peripheral mechanisms, such as reducing skin inflammation and modulation of TRP channels. Resolvin E1 attenuates murine psoriatic dermatitis, a chronic itch disease, by inhibiting migration of cutaneous dendritic cells and gd T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Images were acquired using an inverted fluorescence microscope system (DMI8, Leica) with alternating excitation wavelengths of 340 and 380 nm. The 340 nm/380 nm fluorescence intensity ratio [ R (340/380)], measured with the PCI software every 2 s, was applied as an intracellular calcium concentration ([Ca 2+ ]i) indicator 40 . If the increase in [ R (340/380)] was equal to or greater than 15% of baseline, neurons were considered to be responsive to a particular chemical stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…One study found that TRPC3 agonism induced histamine-independent itch and TRPC3 knockout mice had significantly decreased spontaneous scratching behaviors. Additional research is needed on the therapeutic benefits of targeting TRPC channels [61].…”
Section: Trp Cannonical 3 and 4 (Trpc3 Trpc4)mentioning
confidence: 99%